The influence of instagram content on the shopping behavior of women's clothing products in women's generation z mediated by consumer network behavior - Rache Gavriela (Institute of Computer Science (IOCS), 2023)
The purpose of this research is to examine how Instagram content influences generation Z women's buying behavior for apparel, with a focus on the mediating impact of consumer network activity. This study gathered information from a poll sent to Instagram's active user base among women of generation Z. Path analysis was used to investigate the connection between the researched variables by analyzing the acquired data statistically. The research shows that among women of Generation Z, Instagram has a substantial impact on their purchasing decisions related to apparel. According to these findings, engaging and relevant Instagram content is crucial to capturing the attention and driving purchases from women of Generation Z. It is crucial for brands and online store accounts to make smart use of consumer network activity to assist customers towards more successful purchase choices in light of the plethora of information accessible via social networks. Understanding how Instagram content and online interaction can shape the shopping behavior of Generation Z women is important for marketers and sellers in the modern era, as it allows them to develop more effective marketing and communication strategies.